(untitled) (Bioscience Journal, 2015)
Pawpaw (Carica papaya L.), also known papaya, is a fruit species with economic and social importance for Brazil, the second main world producer. Although this characteristic the relationship between N and K nutrition and papaya fruit quality has been poorly studied. Thus, an objective with this study was to evaluate the effect of nitrogen and potassium for papaya (pawpaw) fruit quality produced in North eastern Brazil. The experimental design consisted of randomised blocks, with treatments distributed in a factorial arrangement (4 x 4), using four nitrogen doses (320, 400, 480 and 560 g of N plant-1) and four potassium doses (380, 475, 570 e 665 g of K2O plant-1), containing with four replications of three plants each. The fruit characteristics, such as fruit mass, titratable acidity, soluble solids, pulp pH and fruit length and width, were recorded. The fruit qualityof pawpaw depend on nitrogen and potassium leaf concentration. The higher fruit quality parameters regarding to soluble solids, pH, fruit length and fruit mass are associated to 45.30 g kg-1 leaf N concentration and 37.55 leaf K concentration.